Proposta de Aplicação do Pagamento por Serviços Ambientais na Bacia do Rio Canoas em Franca - SP - Barbosa, Caroline Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
This research is part of the Canoas River Hydrographic Basin, in the municipality of Franca - SP, where the Canoas River Environmental Protection Area (EPA) is located. The Canoas River Basin is of great importance to the region, being the main supply source for Franca – SP, however, a large part of its water Permanent Preservation Areas (PPAs) are in a degraded state. Knowing the importance of native vegetation around water courses, as it improves the quality and quantity of water, the Payment for Environmental Services (PES) for water was created, which seeks to encourage owners of rural areas who own these areas to provide environmental services for the restoration, protection and conservation of riparian forests. The objective of this research is to propose PES application in the EPA of Rio Canoas, in the municipality of Franca, in São Paulo. The methodology applied is qualitative, exploratory and quantitative in nature, with the study of PES calculations, application methodologies and existing legislation. This work resulted in strategic planning for the application of the PSA to indicate the application of the public policy on Payment for Environmental Services based on a draft municipal Bill, which presents the calculation methodology for each situation that may be encountered and the contract service provision that can be established between provider and payer. Therefore, this work concluded that it is possible to apply PSA in the Canoas River Basin in Franca – SP, and that this program can help protect the basin's water resources, resulting in an improvement in the quality and quantity of water supply public.

Essa pesquisa se insere na Bacia Hidrográfica do Rio Canoas, no município de Franca - SP, onde fica localizada a Área de Proteção Ambiental (APA) do Rio Canoas, criada no artigo 55 da Lei Municipal nº 09 de 1996. A Bacia do Rio Canoas demonstra grande importância para a região, sendo o principal manancial de abastecimento de Franca – SP, entretanto, boa parte de suas Áreas de Preservação Permanentes (APPs) hídricas se encontram em estado degradado. Sabendo da relevância da vegetação nativa no entorno dos cursos d’água, visto que esta melhora a qualidade e a quantidade da água, foi criado o Pagamento por Serviços Ambientais (PSA) das águas, que procura incentivar proprietários de áreas rurais que possuam essas áreas para que prestem serviços ambientais de restauração, proteção e conservação das matas ciliares. O objetivo desta pesquisa é a proposta de aplicação PSA na APA do Rio Canoas, no município de Franca, em São Paulo. A metodologia aplicada é de natureza qualitativa, exploratória e quantitativa, com o estudo de cálculos do PSA, metodologias de aplicação e legislações existentes. Este trabalho resultou no planejamento estratégico de aplicação do PSA para indicar a aplicação da política pública de Pagamento por Serviços Ambientais a partir de uma minuta de Projeto de Lei municipal, a qual apresenta a metodologia de cálculo para cada situação que pode ser encontrada e o contrato de prestação de serviços que pode ser estabelecido entre provedor e pagador. Com isso, este trabalho concluiu que é possível ser aplicado o PSA na Bacia do Rio Canoas em Franca – SP, e que este programa poderá auxiliar na proteção dos recursos hídricos da bacia, ocasionando em uma melhoria na qualidade e na quantidade de água de abastecimento público.
Proposal for Application of Payment for Environmental Services in the Canoas River Basin in Franca - SP
Keywords: Recursos hídricos; Desenvolvimento sustentável; Restauração ecológica; Water resources; Sustainable development; Ecological restoration